Simulation of Two-Dimensional Photonic Crystal Absorption Layers Based on GaAs Matrixes With LiNbO3 Scattering Elements for Solar Cells - Yu Song; Jiajia Quan; Feng Yuan; Zhijie Bi; Yong Wan (International Journal of Chemical Engineering)
In this work, a two-dimensional (2D) photonic crystal (PC) absorption layer is designed for solar cells based on bandgap-tunable and low-cost gallium arsenide (GaAs) with lithium niobate (LiNbO3) as scatterers. The effects of scatterer shape, arrangement, and thickness on the absorption efficiency and photoelectric conversion efficiency (PCE) of the absorption layer are systematically investigated. All simulations are performed using rigorously coupled wave analysis (RCWA) method analysis with incident light in the wavelength range of 0.30–0.80 μm. The simulation results demonstrate that the optimal performance can be yielded when adopting LiNbO3 hexagonal scatterers with a triangular lattice configuration. Compared to the air-hole–based layer, the absorption efficiency of the LiNbO3 scatterer–based layer is increased by 4.70% along with the PCE of above 98%. These results show a huge potential to enhance the efficiency of large-scale solar cells by using cost-effective perovskite materials and promote promising applications of solar cells in the fields of miniaturization and intellectualization.